2012
DOI: 10.1136/jnnp-2012-302451
|View full text |Cite
|
Sign up to set email alerts
|

Charcot–Marie–Tooth disease: frequency of genetic subtypes and guidelines for genetic testing

Abstract: Background Charcot-Marie-Tooth disease (CMT) is a clinically and genetically heterogeneous group of diseases with approximately 45 different causative genes described. The aims of this study were to determine the frequency of different genes in a large cohort of patients with CMT and devise guidelines for genetic testing in practice. Methods The genes known to cause CMT were sequenced in 1607 patients with CMT (425 patients attending an inherited neuropathy clinic and 1182 patients whose DNA was sent to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
286
15
16

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(349 citation statements)
references
References 27 publications
32
286
15
16
Order By: Relevance
“…15,16 Interestingly, GDAP1, the most frequent genetic cause for CMT4, encodes a protein anchored to the mitochondrial outer membrane, thus demonstrating that mitochondrial disorders may manifest with demyelinating polyneuropathy as the predominant feature. 1,[15][16][17] The SURF1 gene encodes one of at least 6 assembly factors of COX, the terminal component of the MRC. Studies on yeast and human mutant cells indicate for SURF1 a role in the formation of the early subcomplexes of COX.…”
Section: Characteristics Of the Cmt4 Index Familymentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Interestingly, GDAP1, the most frequent genetic cause for CMT4, encodes a protein anchored to the mitochondrial outer membrane, thus demonstrating that mitochondrial disorders may manifest with demyelinating polyneuropathy as the predominant feature. 1,[15][16][17] The SURF1 gene encodes one of at least 6 assembly factors of COX, the terminal component of the MRC. Studies on yeast and human mutant cells indicate for SURF1 a role in the formation of the early subcomplexes of COX.…”
Section: Characteristics Of the Cmt4 Index Familymentioning
confidence: 99%
“…This finding is relevant because molecular defects are currently detected in less than 20% of CMT4 patients. 14,15 In both families, a mitochondrial etiology of the disease had not been initially considered because the phenotype consisted of isolated peripheral neuropathy, with very little additional multisystem involvement.…”
Section: Characteristics Of the Cmt4 Index Familymentioning
confidence: 99%
“…More recent studies in large cohorts of patients confirmed that most CMTs are demyelinating but lowered its prevalence to approximately half of all cases, while the prevalence of axonal forms was assessed to be less than one-third, i.e. 17.6-27.1% [Foley et al, 2012;Murphy et al, 2012]. Moreover, the proportion of axonal or demyelinating CMT seems to depend on the geographical area, the structure of the population and the frequency of CMT in the general population.…”
mentioning
confidence: 99%
“…As Fig. 1 shows, once the mode of inheritance was taken under consideration, searching for the relevant mutations covered most of the mutations in the studied population (10 ).…”
Section: Discussionmentioning
confidence: 99%